EVIDENCE FOR BATESIAN MIMICRY IN A POLYMORPHIC HOVERFLY. (10th January 2014) - Edmunds, Malcolm; Reader, Tom
<x xml:space="preserve">Abstract</x> Palatable Batesian mimics are avoided by predators because they resemble noxious or defended species. The striking resemblance of many hoverflies to noxious Hymenoptera is a "textbook" example of Batesian mimicry, but evidence that selection by predators has shaped the evolution of hoverfly patterns is weak. We looked for geographical and temporal trends in frequencies of morphs of the polymorphic hoverfly Volucella bombylans that would support the hypothesis that these morphs are Batesian mimics of different bumblebee species. The frequency of the black and yellow hoverfly morph was significantly positively related to the frequency of black and yellow bumblebees across 52 sites. Similarly, the frequency of the red‐tailed hoverfly morph was positively related to the frequency of red‐tailed bumblebees. However, the frequencies of hoverfly morphs were positively spatially autocorrelated, and after controlling for this, only one of the two common hoverfly morphs showed a significant positive relationship with its putative model. We conclude that the distribution of V. bombylans morphs probably reflects geographical variation in selection by predators resulting from differences in the frequencies of noxious bumblebee species.